SIRPα maintains macrophage homeostasis by interacting with PTK2B kinase in Mycobacterium tuberculosis infection and through autophagy and necroptosis - Wang, Di; Lin, Yunkai; Xu, Feihong; Zhang, Hui; Zhu, Xiaoyan; Liu, Zhen; Hu, Yuan; Dong, Guanjun; Sun, Bingqi; Yu, Yanhong; Ma, Guoren; Tang, Zhigang; et al. (EBioMedicine, 2022)
To determine whether SIRPα can be a diagnostic marker of pulmonary tuberculosis (PTB) and the molecular mechanism of SIRPα regulating macrophages to kill Mycobacterium tuberculosis (MTB). Meta-analysis combined with subsequent qRT-PCR, western-blotting and flow cytometry assay were used to detect SIRPα expression in PTB patients. Cell-based assays were used to explore the regulation of macrophage function by SIRPα. SIRPα−/- and wide type macrophages transplanted C57BL/6J mice were used to determine the function of SIRPα on MTB infection in vivo. SIRPα levels are closely correlated with the treatment outcomes among PTB patients. Cell-based assay demonstrated that MTB significantly induces the expression of SIRPα on macrophages. SIRPα deficiency enhances the killing ability of macrophages against MTB through processes that involve enhanced autophagy and reduced necroptosis of macrophages. Mechanistically, SIRPα forms a direct interaction with PTK2B through its intracellular C-terminal domain, thus inhibiting PTK2B activation in macrophages. Necroptosis inhibition due to SIRPα deficiency requires PTK2B activity. The transfer of SIRPα-deficient bone marrow-derived macrophages (BMDMs) into wild type mice resulted in a drop of bacterial load in the lungs but an enhancement of inflammatory lung damage, and the combination of ulinastatin and SIRPα−/−→WT treatment could decrease the inflammation and maintain the bactericidal capacity. Our data define SIRPα a novel biomarker for tuberculosis infection and underlying mechanisms for maintaining macrophage homeostasis. This work was financially supported by the Chinese National Natural Science Foundation project (No.81401635). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.